Primary Pleural Epithelioid Hemangioendothelioma Compressing the Myocardium. Issue 3 (1st April 2013) - Yu, Lei; Gu, Tianxiang; Xiu, Zongyi; Shi, Enyi; Zhao, Xiaoqi
Abstract Epithelioid haemangioendothelioma (EH) is a rare malignant tumor of vascular origin that usually arises in bone, liver, soft tissue, or lung. EH originating in the pleura has been less frequently described. We describe an uncommon case of pleural EH compressing the myocardium in a 39‐year‐old woman. The patient was diagnosed with pleural EH confirmed by surgery and immunohistochemistry. She sustained stable disease 14 months after the diagnosis and her symptoms improved after systemic chemotherapy with carboplatine and etoposide. Complete surgical excision of pleural EH followed chemotherapy may prolong survival. doi: 10.1111/jocs.12094 (J Card Surg 2013;28:266–268)